2021
DOI: 10.1002/adbi.202000248
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Nanopillars Induce Increased Paxillin Adhesion Assembly and Promote Axon Growth in Primary Cortical Neurons

Abstract: The complexity of the extracellular matrix consists of micro‐ and nanoscale structures that influence neuronal development through contact guidance. Substrates with defined topographic cues mimic the complex extracellular environment and can improve the interface between cells and biomedical devices as well as potentially serve as tissue engineering scaffolds. This study investigates axon development and growth of primary cortical neurons on OrmoComp nanopillars of various dimensions. Neuronal somas and neurit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…In literature, it is reported that well-ordered NW arrays can generate guiding forces to polarize cells or to direct neurite growth. 41,[54][55][56][57]75,98 Many array parameters were modified in these studies, but in the end, primarily the spacing of the nanostructures was contributing decisively, and guiding only occurs within a certain range of array pitches. Nonetheless, a direct comparison can only be made with Bucaro et al because they used comparable array pitches from 0.8 to 5 µm (but only at a fixed NW length of 5 µm) to fine-tune the polarization of human mesenchymal and rodent stem cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, it is reported that well-ordered NW arrays can generate guiding forces to polarize cells or to direct neurite growth. 41,[54][55][56][57]75,98 Many array parameters were modified in these studies, but in the end, primarily the spacing of the nanostructures was contributing decisively, and guiding only occurs within a certain range of array pitches. Nonetheless, a direct comparison can only be made with Bucaro et al because they used comparable array pitches from 0.8 to 5 µm (but only at a fixed NW length of 5 µm) to fine-tune the polarization of human mesenchymal and rodent stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43] Furthermore, NW arrays have been used to measure mechanical properties, [44][45][46] to interact with the cell's nucleus, 47 to constrain movement and spreading, [48][49][50][51][52] or to direct cell polarization such as outgrowth of neurites. [53][54][55][56][57] In addition to the aforementioned passive applications, functionalized NW arrays were employed to incorporate an executing role, such as drug delivery, 29,[58][59][60][61][62][63] cell transfection, [64][65][66][67] electrical stimulation/sensing, [68][69][70][71][72] or biosensing, 73 to name a few. To address specific applications, the interaction of the cell and the NWs can be tuned by adjusting the length and diameter of the NWs and the pitch of the array.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, growing neurites seemed to have a greater alignment in the higher pillars due to their stronger confinement. All in all, the topography resulted in longer axons compared to culture on flat surfaces [20].…”
Section: Topographical Effect On Neurons and Neuron-like Cell Functio...mentioning
confidence: 88%
“…2e) [18]. Similarly, Milos et al examined whether a different topography pattern could promote axonal growth of E18 rat embryo cortical neurons [20]. To do so, they produced a nanopillar silicon mold based on electron beam lithography of photoresist with variable diameters (500, 750, and 1000 nm) and heights (100 and 400 nm).…”
Section: Topographical Effect On Neurons and Neuron-like Cell Functio...mentioning
confidence: 99%
“…Here, the stabilization of the cell–electrode interface is achieved by the topography-induced formation of organized actin rings around the stalk of the engulfed microstructure. 168 , 184 186 The ability of protruding electrodes to induce the shape rearrangement necessary for the cell to accommodate the pseudo-3D structures was further confirmed by recent observations on the topography-driven recruitment of curvature sensitive proteins (e.g., Bin/Amphiphysin/Rvs (BAR) proteins) at the cell–material interface, 177 , 187 as shown in Figure 7 A. Among these, F-actin typically accumulates at nanopillars tips, 188 where high positive curvature is strongly induced by the pseudo-3D geometry.…”
Section: Engineering the Electrical Bio-interface With Pseudo-3d Nano...mentioning
confidence: 99%